DESIGN OF THE POLLUTION GAS CARBON MONOXIDE (CO) MONITORING SYSTEM BASED ON MICROCONTROLLER - Erna Kusuma Wati; Fitria Hidayanti; Novi Azman (Program Studi Fisika Universitas Negeri Jakarta, 2020)
Carbon monoxide is a flammable gas and very toxic to humans, to determine the concentration of carbon monoxide (CO) gas requires a tool that can measure the concentration of the gas. The design of the CO gas monitoring measuring instrument in this study has dimensions of 11cm x 8.6 cm x 2.9 cm using the MQ-135 sensor, Arduino Uno microcontroller to control and process the signal, to display temperature and humidity with a 4.2 Inch LCD. Krisbow KD09-224 Carbon Monoxide Meter is a comparison tool or calibrator, against our monitoring gauges. Testing by experimenting as much as 15 times, to determine the value of the measurement uncertainty. Based on the results of the data when testing, the average amount of measurement = 103.33, with a standard deviation δ 1.29, and the uncertainty value of the measurement results is 0,33 %. Thus the system can be used as monitoring of CO gas pollution in units of ppm (parts per million).